Dynamic modeling and motion precision analysis of spacecraft manipulator with harmonic drive considering the alternate thermal field in orbit. (January 2015) - Zhao, Jieliang; Wu, Jianing; Yan, Shaoze; Li, Junlan; Gu, Yongxia
Nowadays, the harmonic drive is widely used as the reducer in the spacecraft manipulator, which may influence the dynamical properties of flexible spacecraft manipulator. The alternative thermal environment makes the spacecraft manipulator to experience periodic heating and cooling in the sunlight and shadow region of the Earth. The analysis of dynamic modeling and motion precision of flexible spacecraft manipulator with harmonic drive, considering the alternate thermal field in orbit is of significant importance for spacecraft manipulator designers in the early stage of design. The thermal load influences the motion precision, which reflects whether the mechanism is performed normally or not. In order to evaluate the loss of motion precision, this paper establishes the dynamical model of spacecraft manipulator with harmonic drive considering the alternate thermal field in orbit. A thermal analysis model of flexible spacecraft manipulator with harmonic drive is developed to characterize the thermal response of the whole spacecraft manipulator system subjected to space heat flux. Two different altitudes including low Earth orbit and geosynchronous Earth orbit are considered. Moreover, the transient temperature fields in different orbits of spacecraft manipulator and the effects of the thermal environment factors on the spacecraft manipulator are investigated. Simulation results reveal the evolution process of the transient temperature field of the spacecraft manipulator system. According to the results, the maximum temperature difference for space manipulator can lead to more severe precision loss compared with the minimum temperature difference. In addition, the vibration frequency of angular velocity error is determined by the maximum thermal heat flux. The proposed method is useful for forecasting the temperature distribution of the spacecraft manipulator system, and will provide meaningful information for performance enhancement of the aerospace facilities.